Effect of vertical distance of geogrid layers on slope stability. Issue 1 (September 2020) - Chairullah, B; Yunita, H; Munirwansyah, M; Ambiya, R
Abstract: The landslide that occurred on the Meulaboh - Geumpang road section on May 10, 2017, resulted in the interruption of land transportation connecting West Aceh Regency and Pidie Regency, Aceh Province. The landslide on this road had an impact on the obstruction of logistics distribution and other needs from the direction of Meulaboh to Geumpang and vice versa. Based on these problems, the appropriate solution is needed in the prevention and planning of slopes to prevent landslides from happening again. This research was carried out by analyzing the slope stability under natural slope conditions and analyzing the slope stability of the conditions given slope reinforcement in the form of geogrids. Slope stability analysis is performed using the finite element method. The slopes are given alternative geogrid reinforcement with varying vertical distances. The variation of vertical geogrid distance is adjusted to the condition of the curve of the natural slope collapse before reinforcement. Based on the analysis of slope stability for natural conditions without reinforcement (existing condition), the safety factor values (SF) obtained at STA 84 + 280 and STA 84 + 910 were respectively 1.14 and 1.16. The results of the analysis of the slope stability that has been given reinforcement show that the vertical geogrid distance influences the slope safety factor.